Amyloid Beta monomers regulate cyclic adenosine monophosphate response element binding protein functions by activating type‐1 insulin‐like growth factor receptors in neuronal cells. Issue 1 (1st November 2017) - Zimbone, Stefania; Monaco, Irene; Gianì, Fiorenza; Pandini, Giuseppe; Copani, Agata G.; Giuffrida, Maria Laura; Rizzarelli, Enrico
Summary: Alzheimer's disease (AD) is a progressive neurodegenerative disorder associated with synaptic dysfunction, pathological accumulation of β‐amyloid (Aβ), and neuronal loss. The self‐association of Aβ monomers into soluble oligomers seems to be crucial for the development of neurotoxicity ( J. Neurochem ., 00, 2007 and 1172). Aβ oligomers have been suggested to compromise neuronal functions in AD by reducing the expression levels of the CREB target gene and brain‐derived neurotrophic factor (BDNF) ( J. Neurosci ., 27, 2007 and 2628; Neurobiol. Aging, 36, 2015 and 20406 Mol. Neurodegener ., 6, 2011 and 60). We previously reported a broad neuroprotective activity of physiological Aβ monomers, involving the activation of type‐1 insulin‐like growth factor receptors (IGF‐IRs) ( J. Neurosci ., 29, 2009 and 10582, Front Cell Neurosci ., 9, 2015 and 297). We now provide evidence that Aβ monomers, by activating the IGF‐IR‐stimulated PI3‐K/AKT pathway, induce the activation of CREB in neurons and sustain BDNF transcription and release.